De dentro para fora e de fora para dentro: um estudo sobre o itinerário formativo dos alunos participantes do programa de aprendizagem - Moraes, Camila Geórgia de (2021)
The Apprenticeship Act is provided in the Consolidation Laws of Labor (CLT) and was modernized through Laws 10.097, of December 19.2000; 11.180, of September 23, 2005; and 11.788, of September 25, 2008. Its main objective is to create opportunities for teenagers and young people, between 14 and 24 years old, to enter the labor market. At the same time that it aims to ensure a comprehensive education for the student, it qualifies the workforce, through training institutions, and contributes to income generation. Considering the aspects of personal, professional and social development proposed in the Professional Learning course, this research aimed to analyze the previous school trajectories of young apprentices. The intention was to investigate the relationship of this public policy with the life project of students in the Senac Learning Program, in the Professional Learning course in Commerce of Goods, Services and Tourism, at Senac São Paulo. To carry out this study, we chose to select one of Senac's school units, located in the far east of the capital. It is a research composed of three phases with mixed methods with sequential explanatory design that collected and analyzed descriptive and quantitative data using a questionnaire, qualitative data with conversation circles and secondary data with materials produced by the learners. The first phase consisted of the application of a questionnaire with 25 closed and multiple choice questions based on the IBGE criteria, considering the social and multidomain statistical groups. The second phase consisted of conversation circles with open dialogues and defined themes, whose purpose was to reveal social subjectivities through mediation. And finally, we selected three activities carried out in the classroom to probe and add to the previous analysis. One of the selection criteria was the period of the students in the Program, contemplating apprentices in the initial stage (from 1 to 5 months), intermediate (7 to 10 months) and final (13 to 16 months), in addition to age diversity. The data obtained in the research allowed us to glimpse a youth that struggles to be the protagonist of their history, despite the contextual difficulties and the scarcity of public policies and programs that meet their real needs. The results show the reasons that lead them to join the Learning Program, how this experience contributes to their trajectory and to their life project, and which topics, from the Program's own law and guidelines, need to be revised.